HIGH ALTITUDE PULMONARY HYPERTENSION («MIRRAKHIMOV'S DISEASE») - A. Sh. Sarybaev; A. S. Sydykov; M. A. Sartmyrzaeva; A. M. Maripov; A. T. Mamazhakypov; A. Ch. Akunov (Евразийский Кардиологический Журнал)
SUMMERY It is estimated, that more than 140 million people reside at altitudes above 2500 m in 35 countries worldwide. High altitude residents display moderate erythrocytosis and mild-to-moderate elevation in pulmonary artery pressure. Howevere, in some indivudals, severe pulmonary hypertension develop with ensuing right ventricular hypertrophy and failure and thus representing a major public health problem in mountainous regions around the world. In this review, we discuss the history of discovery, clinical findings, diagnostic, treatment and prevention of the disease. Key words: hypoxia, high altitude, pulmonary artery pressure, pulmonary hypertension, right ventricular hypertrophy.